173 TRANSFORMING GROWTH FACTOR-BETA STIMULATION OF LUNG INFLAMMATORY CELLS FROM PRETERM INFANTS DOES NOT INDUCE MATRIX METALLOPROTEINASE-9. (1st January 2005) - Aghajanian-Parks, K.; Literat, A.; Kwong, K.; Ramanathan, R.; Minoo, P.
Abstract : Objective: Transforming growth factor-beta (TGF-beta) plays an important role in normal lung development and function and tissue remodeling following injury. We have previously shown that high initial levels of TGF-beta and its persistence over time in the lungs of preterm infants contribute to development of bronchopulmonary dysplasia (BPD) and predict the need for oxygen therapy at home. It is also known that matrix metalloproteinases (MMPs) play an important role in degradation of extracellular matrix and basement membranes, thereby potentially contributing to pathogenesis of BPD. The aim of our study was to determine whether TGF-beta activates production of MMP-9 in lung inflammatory cells from preterm infants. Methods: Tracheal aspirate fluid (TAF) samples were collected from intubated infants (gestational age 31-40 weeks) during their 2nd and 3rd postnatal days. The lung inflammatory cells were isolated and placed in cell culture media with or without varying doses of recombinant human (rh) TGF-beta. ELISA was used to measure the level of MMP-9 in each sample. Results: MMP-9 was detected in all samples examined with a wide range of 8 to 45 nanograms/ml/5×105 cells. There were no detectable differences found in the level of MMP-9 in inflammatory cells treated with rhTGF-beta as compared to the control. Conclusions: Inflammatory cells are a major source of MMP-9. TGF-beta does not appear to activate production of MMP-9 by these cells in culture. Alternatively, because of exposure to high levels of TGF-beta in vivo, production of MMP-9 may be maximally stimulated. Further studies are underway to distinguish between these two possibilities.